(untitled) (Applied Biological Research, 2023)
Leukemia is one of the most common cancer types that affects both adults and children. The purpose of current study was to assess the demographic status of adult leukemic patients among Kurdish population in Iraq. The records of 484 adult patients at Hiwa Cancer Hospital in Sulaymaniyah, Kurdistan region (Iraq) between January 2015 and December 2020 were the subject of this retrospective descriptive analysis. The differenttypes of cancer observed at Hiwa Cancer Hospital were acute lymphatic leukemia (ALL), acute myeloblastic leukemia (AML), chronic lymphatic leukemia (CLL), and chronic myeloid leukemia (CML). There were 307 male and 177 female cancer patients (ratio 1.734:1), with age range between 16 and 98 years and mean age of 54.49 years. It was found that 291 (60.1%) patients were non-educated, while 109 (22.5%), 34 (7.0%), and 50 (10.3%) patients were tertiary, post-basic and basic educated, respectively. Based on the employment status, 276 (57.0%) patients were unemployed, 145 (37.0%) employed, and 63 (13.0%) were retired. It was found that both educational status and employment status were correlated with leukemia incidence at p value equal to 0.0001 and 0.002, respectively.